The role of chemokines in ocular diseases. Part II. Participation of chemokines in ocular diseases - Malesiński, Roman; Mrugacz, Małgorzata; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
The chemokines are family of ca. 50 chemotactic cytokines produced by leucocytes and tissue cells, which regulate and stimulate leucocytes migration. Dysregulation of this process is apparent in chronic inflammation, allergic eye disease, corneal graft rejection, proliferative vitreoretinopathies and age-related macular degeneration. Antagonists of chemokine receptors have demonstrated anti–inflammatory and antiviral activity and may represent new generations of therapeutic agents.